Food Security and Climate Change Impacts on Nutrition: Exploring Vulnerabilities in Food Systems and Their Health Consequences - Muh. Aniar Hari Swasono; Carlos Chavarria; Olivia Jimenez (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Climate change has emerged as a major threat to global food security, profoundly affecting food availability, accessibility, utilization, and stability, with direct consequences for human nutrition and health. Disruptions in food systems caused by rising temperatures, extreme weather events, and environmental degradation have intensified nutritional vulnerabilities, particularly among low-income and climate-sensitive populations. Purpose. This study aims to explore how climate change impacts food systems and to assess the resulting nutritional and health consequences across different socio-economic contexts. Method. A mixed-methods approach was employed, combining secondary data analysis from global food security, climate, and nutrition databases with a systematic review of peer-reviewed literature and international reports. Descriptive and comparative analyses were used to identify patterns of vulnerability, while thematic analysis was applied to examine pathways linking climate stressors, food systems, and nutritional outcomes. Results. The results indicate that climate change significantly undermines food system resilience, leading to reduced dietary diversity, increased micronutrient deficiencies, and heightened risks of malnutrition. The impacts are most pronounced in regions with limited adaptive capacity and weak food governance structures. Conclusion. The study concludes that strengthening food system resilience through climate-adaptive policies, sustainable agricultural practices, and integrated nutrition strategies is essential to mitigate health risks and ensure long-term food security in a changing climate.